Targeted Stimulation of Micropores by CS2 Extraction on Molecular of Coal - Zhang, Zhen; Liu, Gaofeng; Wang, Xiaoming; Lin, Jia; Barakos, George; Chang, Ping (MDPI AG, 2024)
The targeted stimulation of micropores based on the transformation of coal’s molecular structure is proposed due to the chemical properties and difficult-to-transform properties of micropores. Carbon disulfide (CS2) extraction is used as a targeted stimulation to reveal the internal evolution mechanism of micropore transformation. The variations of microcrystalline structures and micropores of bituminous coal and anthracite extracted by CS2 were analyzed with X-ray diffraction (XRD), low-temperature carbon dioxide (CO2) adsorption, and molecular simulation. The results show that CS2 extraction, with the broken chain effect, swelling effect, and aromatic ring rearrangement effect, can promote micropore generation of bituminous coal by transforming the microcrystalline structure. Furthermore, CS2 extraction on bituminous coal can decrease the average micropore size and increase the micropore volume and area. The aromatic layer fragmentation effect of CS2 extraction on anthracite, compared to the micropore generation effect of the broken chain effect and swelling effect, can enlarge micropores more remarkably, as it induces an enhancement in the average micropore size and a decline in the micropore volume and area. The research is expected to provide a theoretical basis for establishing reservoir stimulation technology based on CS2 extraction.